Identification of KCNQ1 compound heterozygous mutations in three Chinese families with Jervell and Lange-Nielsen Syndrome. (4th May 2017) - Wang, Cuicui; Lu, Yu; Cheng, Jing; Zhang, Lei; Liu, Wei; Peng, Weihua; Zhang, Di; Duan, Hong; Han, Dongyi; Yuan, Huijun
Abstract: Conclusion: Besides expanding the spectrum of KCNQ1 mutations causing Jervell and Lange-Nielsen Syndrome (JLNS), the results showed diversity of its phenotypes, and emphasized the importance of molecular genetic analysis in confirming clinical diagnosis and making diagnosis possible before the emergency symptoms for deaf individuals. Objectives: This study aimed to investigate four patients from three Chinese families with congenital hearing loss clinically and genetically. Method: Genetic analysis of previously reported deafness genes based on massively parallel sequencing was conducted in more than five thousand Chinese hearing loss patients. Detailed clinical features of the patients with compound heterozygous or homozygous mutations of KCNQ1 gene were collected and analyzed. Results: Compound mutations of KCNQ1 were found to be the genetic etiology of four patients from three families. Among the six KCNQ1 mutations, c.546C > A was identified as a novel mutation, c.965C > T had been reported in JLNS, while c.683 + 5G > A, c.1484_1485delCT, c.905C > T and c.1831G > A were previously reported in LQT1. In addition to congenital profound hearing loss in all subjects, two sibling subjects showed typical JLNS cardiac phenotype of prolonged QTc and recurrent syncopal episodes. One subject presented not only JLNS, but also iron-deficiency anemia and epilepsy. The other subject did not present any cardiac phenotype.